Growth and Yield Responses of Four Soybean (Glycine max (l.) Merrill.) Cultivars to Different Methods of NPK Fertilizer Application - Paul Benyamin Timotiwu; Yayuk Nurmiaty; Eko Pramono; Siti Maysaroh (Universitas Muhammadiyah Yogyakarta, 2020)
This study aimed to determine the growth and yield responses of four soybean cultivars to different methods of N, P, and K fertilizers application. The methods consisted of one-time application (at the planting time) and split application (at the planting time and during the initial stage of pod formation (R3 stage)). Four superiors soybean cultivars were used, namely Anjasmoro, Grobogan, Dena-1, and Argomulyo. One-time fertilizers application resulted in an increased plant height compared to split fertilizers application. In contrast, the split fertilizers application led to a higher yield of soybeans indicated by the higher total number of pods, number of filled pods, 100-grain weight, and seed dry weight. Cv. Anjasmoro produced higher growth and yield than cv. Grobogan, Dena-1, and Argomulyo. It also produced the highest yield compared to other cultivars. Meanwhile, cv. Argomulyo produced the lowest yield in both fertilization methods. Based on the soil analysis after harvest, the nutrient content of K in the soil was higher than before planting in both fertilization methods. In addition, the split fertilizers application led to higher utilization of P in the soil after harvest.